Civil Liability Insurance for Doctors in Algerian Legislation - BELDJEDOUI, Besma (Journal of Human Sciences, 2025)
Like other lawmakers, the Algerian lawmaker has ordered that physicians, surgeons, civilian healthcare facilities, and all other professionals in the medical, paramedical, and pharmaceutical fields get insurance that covers their civil liability for any mistakes they may make while carrying out their duties as professionals throughout the course of treatment. The hazards connected to using medical equipment and gadgets while practicing medicine are also covered by this insurance. The goal of requiring medical professionals to carry civil liability insurance is twofold: first, to reimburse patients who may sustain harm as a result of medical errors, and second, to give physicians the protection they need to carry out their jobs in a secure and confident environment.